Motivation for physical activity in children: A moving matter in need for study - Pannekoek, Linda; Piek, Jan Patricia; Hagger, Martin (Elsevier BV; North Holland, 2013)
Motivation for physical activity in children below the age of 12 years is a largely underrepresented issue in contemporary research. Although engagement in sufficient physical activity is highly important for children’s current and later health, relatively little is known of the factors that motivate children to be physically active. Various theories have been developed in an attempt to explain motivation toward physical activity in adults. Recent developments have focussed on integrating constructs of these theories in order to attain a comprehensive account of motivated behavior. The relationships between different motivational constructs have generally been investigated in healthy adolescents and adults. This manuscript outlines why more theoretically driven research into children’s motivation toward physical activity is needed. Constructs stemming from various motivational theories and their interrelationship as evidenced in youth and adults will be summarized. The current state of research on the applicability of these motivational constructs to children, and the generalizability of the interrelationship between the constructs to child samples will be outlined. A deeper insight into the motivational determinants of physical activity participation in children could inform the design of interventions to facilitate the development of physically active lifestyles that persist at older ages.